Categories of Information Need Expressed by Parents of Individuals with Rare Genetic Disorders in a Facebook Community Group: A Case Study with Implications for Information Professionals. Issue 1 (2nd January 2020) - Wang, Ting; Lund, Brady
Abstract: Costello syndrome is a rare genetic disorder that affects virtually all aspects of an individual's life. Few specialists have been trained to understand the condition and provide guidance to caregivers and virtually no traditional information sources (e.g. books, websites) exist to provide information to caregivers. In this case, the community becomes a major source of information for caregivers of individuals with this condition. This study examines the types of information that need to be expressed in one of these communities: an online Facebook group. The categories of information need to be identified in the study to demonstrate areas of concern to caregivers and offer areas for further research or publication for researchers of rare disorders and health conditions. The role of information professionals in satisfying these information needs of caregivers of individuals with Costello syndrome and other rare disorders.